Catalytic reaction engineering - Gunjal, P. R.; Ranade, V. V. (Industrial catalytic processes for fine and specialty chemicals, 2016)
hemical reaction engineering has contributed remarkably in bringing laboratory-developed chemistry into commercial practice. Reaction engineering is useful for analysis of reactions, identifying rate-limiting steps, determining overall rates, selection of reactor configuration and design and scale-up of reactors. Reaction engineering also provides useful insights into catalytic cycles and provides clues for improving catalyst systems. It essentially includes all the activities necessary to evolve best possible hardware and operating protocol for the reactor to carry out the desired transformation of raw materials (or reactants) into value-added products. This chapter provides an overview of reaction engineering aspects of catalytic processes.